Aggregation kinetics of humic acids in the presence of calcium ions - Kloster, Nanci Soledad (2013)
The aggregation kinetic of a humic acid (HA) sample as a function of Ca2+ concentration at pH 5, 7 and 9 was investigated. UV-VIS spectroscopy was employed to quantify the progress of the aggregation reaction and zeta potential measurements were used to evaluate the charging state of the HA molecules. The aggregation rate increases significantly by increasing Ca2+ concentration at all investigated pH, being higher at pH 9 than at pH 5 and 7. An aggregation mechanism is proposed, which consists of at least two steps: a rapid binding of Ca2+ to humic molecules, followed by a slower process where HA molecules approach each other and become aggregated. This aggregation is possible because Ca2+ binding decreases the zeta potential of HA from -37 mV to -15 mV and because it is able to form calcium bridges between HA molecules. There is no molecular fractionation up to 60% of aggregation. Above this value, HA aggregates become enriched with more aromatic HA molecules. The fast aggregation of HA in the presence of calcium ions implies that aggregates may temporarily trap, protect and transport pollutants in the environment.